2006
DOI: 10.1136/gut.2005.072942
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1B proinflammatory genotypes protect against gastro-oesophageal reflux disease through induction of corpus atrophy

Abstract: Background and aims:The relationship between Helicobacter pylori infection and gastro-oesophageal reflux disease (GORD) is controversial but it is accepted that GORD is associated with increased exposure to gastric acidity. The proinflammatory interleukin (IL)-1B polymorphisms increase the risk of hypochlorhydria and gastric atrophy. We examined the association between proinflammatory cytokine gene polymorphisms, presence of gastric atrophy, and risk of GORD in H pylori positive and negative subjects in Japan.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 36 publications
1
47
0
1
Order By: Relevance
“…Some recent researches revealed the association between specific proinflammatory polymorphisms in genes and GERD. IL-1β (-31) polymorphic allele and IL-1RN2 are demontrated to be negatively correlated to GERD (9). In a well organized study it has been shown that there is not any difference of IL-1β (-511) polymorphism among patients with Barrett's esophagus, GERD or gastric adenocarcinoma (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some recent researches revealed the association between specific proinflammatory polymorphisms in genes and GERD. IL-1β (-31) polymorphic allele and IL-1RN2 are demontrated to be negatively correlated to GERD (9). In a well organized study it has been shown that there is not any difference of IL-1β (-511) polymorphism among patients with Barrett's esophagus, GERD or gastric adenocarcinoma (10).…”
Section: Discussionmentioning
confidence: 99%
“…In a well organized study it has been shown that there is not any difference of IL-1β (-511) polymorphism among patients with Barrett's esophagus, GERD or gastric adenocarcinoma (10). Among healthy persons, important inter-individual variations were seen in pro-inflammatory proteins especially in in-vitro production (9). Numerous reseraches have shown the impact of polymorphisms of IL-1β and IL-1RN on the development of GERD (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inverse associations between IL1BÀ511T/À31C and gastroesophageal reflux disease risk have been recently reported (73,74). It is reasonable that alleles associated with gastric cancer and gastric atrophy would also be associated with a decrease in risk of an acid-related condition, such as gastroesophageal reflux disease.…”
Section: Discussionmentioning
confidence: 99%
“…18 Several studies have shown that these polymorphisms, as would be expected, offer relative protection against reflux oesophagitis and its complications in H. pyloriinfected people. [19][20][21] In developed countries, individuals are infected with H. pylori strains of differing pathogenicity. The most pathogenic strains increase the risk of peptic ulceration and gastric adenocarcinoma largely through increasing gastric inflammation, and as the corpus is often involved these strains most commonly suppress acid production.…”
Section: H Pylori and Gord Complications In East Asiamentioning
confidence: 99%